Evaluation of the potential value of the F1H and F2H Diatomaceous earth formulations as grain protectants against Rhyzopertha dominica (Fabricius) (Coleoptera: Bostrichidae) - Liška, Anita; Korunić, Zlatko; Rozman, Vlatka; Lucić, Pavo; Baličević, Renata; Halamić, Josip; Galović, Ines (Julius-Kühn-Archiv, 2018)
An insecticidal efficacy of two newly developed grain protectant formulations were assessed against lesser grain borer Rhyzopertha dominica (Fabricius) (Coleoptera: Bostrichidae) on wheat and corn after 6 months period of. Tested formulations, marked as F1H and F2H, based on inert dust, laurel leaves, lavender essential oil, corn oil, silica gel (both F1H and F2H) and pyrethrin (only F2H) were tested at six doses (from 100 ppm to 600 ppm) depending on formulation and type of grain. The appropriate weights of each formulation, were added seperately to plastic containers containing 10 kg of wheat or corn. An initial population of 200 adults of R. dominica were added into each container and left under natural environmental conditions for up to 6 months. A commercial diatomaceous earth (DE) insecticide, Celatom® Mn 51, was used for the comparison of the results, in addition to the untreated control. After six months, both formulations showed higher insecticidal effect than DE Mn 51 in corn and in wheat. Furthermore, the initial population of R. dominica, introduced in wheat was suppressed almost completely, with only 0.7%-5.3% live adults found, depending on formulations and dose. The order of efficacy was F1H>F2H>DE Mn 51. Similar suppression of the initial population was recorded in corn, where F2H was slightly more effective than F1H with 2.0%-10.6% and 4.1%-9.5% live adults found, respectively. At the same time, in the treatments with DE Mn 51 there were 4.7%-74.7% and 33.4%-56.1% live adults in wheat and corn, respectively.